Risk Management and the Pension Fund industry. (Global Financial Stability Report; Global Financial Stability Report, 2004)
This paper looks at the longer-term challenges pension funds face as population age and key issues to address to enhance their risk management practices and their role as long-term investors. The paper focuses primarily on Japan, the Netherlands, Switzerland, the United Kingdom, and the United States, where funded pension plans are most developed. The size of pension savings in these countries, their projected growth, and the recent development of funded pension schemes in other countries highlight the fast-growing importance of pension funds for international capital markets and to financial stability.